cot A +cosec A-1/cot A -cosec A+1=1+sin A/cos A

Asked by Pallavi tripathy | 22nd Jun, 2013, 01:20: PM

Expert Answer:

LHS

= cosec A + cot A - ( cosec ^2 A - cot ^2 A ) / cot A- cosec A +1

= cosec A + cot A -( cosec A + cot A) ( cosecA - cot A) /cot A - cosecA+1

= (cosec A+ cot A) ( 1- cosec A+ cot A) / cot A-cosec A+1 

= cosec A+ cot A

= 1/sinA + cos A/sinA

= 1+cosA/sinA

Answered by  | 22nd Jun, 2013, 10:56: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.